Value of ctDNA in surveillance of adjuvant chemosensitivity and regimen adjustment in stage III colon cancer: a protocol for phase II multicentre randomised controlled trial (REVISE trial) - Jun Huang; Rui Fan; Ziqiang Wang; Meng Qiu; Jiahao Zhou; Zikai Zhou; Xiangbing Deng; Qingbin Wu (BMJ Open, 2025)
Introduction The standard of care for stage III colon cancer is 3 or 6 months of double-drug regimen chemotherapy following radical surgery. However, patients with positive circulating tumour DNA (ctDNA) exhibit a high risk of recurrence risk even if they receive standard adjuvant chemotherapy. The potential benefit of intensified adjuvant chemotherapy, oxaliplatin, irinotecan, leucovorin and fluoropyrimidine (FOLFOXIRI), for ctDNA-positive patients remains to be elucidated.Methods and analysis This multicentre phase II randomised controlled trial aims to investigate the utility of ctDNA in monitoring chemosensitivity and to preliminarily assess whether intensified chemotherapy with FOLFOXIRI can increase ctDNA clearance and improve survival outcomes. A total of 60 eligible patients with stage III colon cancer exhibiting postoperatively positive ctDNA before and after two cycles of oxaliplatin and capecitabine (XELOX) will be randomly assigned to continue five additional cycles of XELOX (control arm) or switch to eight cycles of FOLFOXIRI (experimental arm). This sequential approach is designed to escalate treatment for patients with persistent ctDNA positivity while avoiding overtreatment in those who may respond well to standard chemotherapy. The primary endpoint is the change in ctDNA concentration, defined as the difference between the ctDNA concentration measured after two cycles of XELOX and after the completion or termination of chemotherapy. Secondary endpoints include the ctDNA clearance rate, 2-year disease-free survival, distant metastasis-free survival, chemotherapy-related side effects and quality of life.Ethics and dissemination This trial has been approved by the Ethics Committee of the West China Hospital, Sichuan University (approval number: 20231998). The findings will be disseminated through peer-reviewed publications and presentations at scientific conferences.Trial registration number ClinicalTrials.gov (NCT06242418, registered on 27 January 2024).